Catchword: Digital Detox - Mirbabaie, Milad; Stieglitz, Stefan; Marx, Julian (Business & Information Systems Engineering)
Keywords: Information Systems

Review of Design-Oriented Green Information Systems Research - Brendel, Alfred Benedikt; Chasin, Friedrich; Mirbabaie, Milad; Riehle, Dennis M.; Harnischmacher, Christine (Sustainability)
Green IS (GIS) research addresses environmental challenges brought on by climate change and the need to preserve the natural environment. Within this scope, design-oriented research, most notably within the Design Science Research (DSR) community, aims to provide solutions to these environmental challenges in the form of novel artifacts. The resulting IS solutions are valuable instruments for reducing emissions, increasing energy efficiency, and mitigating waste. Over the past 14 years, the IS research community was called upon multiple times to focus on designing solutions suitable for facilitating sustainability. However, it is unclear how these calls for action resonated within the design-oriented research community. Against this background, we analyzed the landscape of design-oriented GIS research by looking at 60 different GIS studies that have designed and evaluated an artifact. By analyzing these publications, we were able to make six observations. Based on these observations, we discuss how design-oriented GIS research can evolve to live up to the expectations of creating an immediate positive environmental impact.
Keywords: Management; Monitoring; Policy and Law; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Click me…! The influence of clickbait on user engagement in social media and the role of digital nudging - Jung, Anna-Katharina; Stieglitz, Stefan; Kissmer, Tobias; Mirbabaie, Milad; Kroll, Tobias (PLOS ONE)
Clickbait to make people click on a linked article is commonly used on social media. We analyze the impact of clickbait on user interaction on Facebook in the form of liking, sharing and commenting. For this, we use a data set of more than 4,400 Facebook posts from 10 different news sources to analyze how clickbait in post headlines and in post text influences user engagement. The results of our study revealed that certain features (e.g., unusual punctuation and common clickbait phrases) increase user interaction, whereas others decrease engagement with Facebook posts. We further use our results to discuss the potential role of digital nudging in the context of clickbait. Our results contribute to understanding and making use of the effect of different framings in social media.
Keywords: Multidisciplinary

Rumor Correction in Social Media Crisis Communication: A Case of Connective Sense-Breaking - Mirbabaie, Milad; Marx, Julian; Reimann, Annette (AIS Transactions on Human-Computer Interaction)
Keywords: General Medicine

How News Websites Refer to Twitter: A Content Analysis of Twitter Sources in Journalism - Kapidzic, Sanja; Neuberger, Christoph; Frey, Felix; Stieglitz, Stefan; Mirbabaie, Milad (Journalism Studies)
Keywords: Communication

Trust Me, I’m an Influencer! - A Comparison of Perceived Trust in Human and Virtual Influencers - Hofeditz, Lennart; Nissen, Anika; Schütte, Reinhard; Mirbabaie, Milad (30th European Conference on Information Systems - New Horizons in Digitally United Societies, ECIS 2022, Timisoara, Romania, June 18-24, 2022)

A Design Science Artefact for Cyber Threat Detection and Actor Specific Communication - Eyilmez, Kaan; Basyurt, Ali Sercan; Stieglitz, Stefan; Fuchss, Christoph; Kaufhold, Marc-André; Reuter, Christian; Mirbabaie, Milad (Australasian Conference on Information Systems (ACIS))
Keywords: Student; Security; Projekt-CYWARN

Automating Crisis Communication in Public Institutions–Towards Ethical Conversational Agents That Support Trust Management - Hofeditz, Lennart; Mirbabaie, Milad; Erle, Lukas; Knoßalla, Eileen; Timm, Lara (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

Credibility of Cyber Threat Communication on Twitter–Expert Evaluation of Indicators for Automated Credibility Assessment - Basyurt, Ali Sercan; Fromm, Jennifer; Stieglitz, Stefan; Mirbabaie, Milad (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

From Dark Patterns to Digital Sludging–Mapping the Ethical Debate on Controversial Persuasive System Design - Clausen, Sünje; Marx, Julian; Mirbabaie, Milad; Stieglitz, Stefan (Proceedings of the 43rd International Conference on Information Systems (ICIS))